Sulfur-doped corn silk porous carbon as well as preparation method and application thereof
The preparation of sulfur-doped corn silk porous carbon by one-step activation vulcanization method solves the problems of low efficiency and poor circulation stability of the first circle of biomass carbon materials in sodium ion batteries, and achieves high capacity and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411349933.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-14
AI Technical Summary
The low efficiency and poor circulation stability of biomass carbon materials in the first circle of sodium ion batteries affect their application in sodium ion batteries.
The sulfur-doped corn silk porous carbon is prepared by one-step activation of sulfur-doped corn silk. Through pre-carbonization, ball milling, hydrochloric acid treatment and high-temperature vulcanization, the conductivity and active sites of the material are improved, and the storage performance of sodium ions is enhanced.
It achieves high capacity, good cycle stability and rate performance, and improves the application performance of biomass carbon materials in sodium ion batteries.
Smart Images

Figure CN119306203A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery negative electrode material preparation, and in particular to a sulfur-doped corn silk porous carbon and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have gradually become one of the most common power sources to replace traditional fossil fuels. Due to their long life, high energy density, and light weight, LIBs have been used in various devices in daily life, such as electric vehicles and portable devices including mobile phones, laptops, and power tools. However, LIBs still have their own shortcomings throughout the development process. Global lithium resources are limited, the cost of lithium batteries has increased significantly in recent years, and lithium battery safety issues have occurred frequently. Therefore, sodium-ion batteries (SIBs) have received great attention due to their advantages such as abundant reserves, low cost, and high safety, and can also be used as energy storage batteries.
[0003] Biomass-derived carbon negative electrode materials have the advantages of wide sources, low prices, environmental protection, non-toxicity and excellent performance. In recent years, biomass precursors from various sources have been used to prepare carbon materials, and the application of such carbon materials in the negative electrode of sodium ion batteries has been studied. The research shows that biomass-derived carbon negative electrode materials have many advantages and relatively high sodium storage capacity, but there are still problems such as low first-cycle coulombic efficiency and poor cycle stability and rate performance. Therefore, it is necessary to modify and optimize the existing biomass carbon materials, improve the sodium storage performance of biomass carbon materials, and promote the development of biomass carbon materials in sodium ion batteries. The main optimization methods currently include heteroatom doping, structure and morphology design, and preparation of composite materials. The carbon matrix doped with heteroatom S can effectively enhance the conductivity of the material and improve the characteristics of the electrochemical site, thereby improving Na + storage performance, and the presence of heterocyclic sulfur atoms in carbonaceous materials can increase the number of active sites in the material and promote Na + insertion / extraction, improving the conductivity and specific capacity of SIBs.
[0004] Therefore, the present invention provides a method for preparing a sulfur-doped corn silk porous carbon negative electrode material by using waste biomass corn silk as a carbon source through a one-step activation and sulfurization method to solve the above problems. Summary of the invention
[0005] Based on the above, the purpose of the present invention is to provide a sulfur-doped corn silk porous carbon and its preparation method and application, to prepare a sulfur-doped corn silk porous carbon with simple process, low cost and high capacity, effectively improve the first-cycle coulombic efficiency and sodium storage performance, and realize the application of biomass carbon materials in high-capacity sodium ion batteries.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing sulfur-doped corn silk porous carbon comprises the following steps:
[0008] The corn silk is washed, dried, and crushed as a carbon source, and pre-carbonized to obtain a precursor A;
[0009] Ball milling the precursor A to obtain a precursor B;
[0010] The precursor B is mixed with hydrochloric acid and stirred, washed with ultrapure water until neutral, and dried to obtain a precursor C;
[0011] The precursor C and sulfate are fully ground and treated at high temperature to obtain sulfur-doped corn silk porous carbon without impurities being removed;
[0012] The unremoved sulfur-doped corn silk porous carbon is ultrasonically treated with hydrochloric acid, washed with ultrapure water until neutral, and dried to obtain sulfur-doped corn silk porous carbon.
[0013] As a preferred solution of the method for preparing sulfur-doped corn silk porous carbon, the particle size of the carbon source is 300-600 meshes.
[0014] As a preferred solution of the method for preparing sulfur-doped corn silk porous carbon, the pre-carbonization temperature is 250-400° C., and the carbonization time is 2-5 hours.
[0015] As a preferred embodiment of the method for preparing sulfur-doped corn silk porous carbon, when the precursor A is ball-milled, the ball-milling time is 1 to 6 hours and the rotation speed is 400 to 600 r / min.
[0016] As a preferred embodiment of the method for preparing sulfur-doped corn silk porous carbon, when the precursor B is mixed and stirred with hydrochloric acid, the concentration of the hydrochloric acid is 0.5 to 3 mol / L, the stirring temperature is 60 to 80° C., and the stirring time is 12 to 24 h.
[0017] As a preferred embodiment of the method for preparing sulfur-doped corn silk porous carbon, the mass ratio of the sulfate to the precursor C is (0.5-2.5):1.
[0018] As a preferred method for preparing sulfur-doped corn silk porous carbon, the precursor C is fully ground with potassium sulfate and then subjected to high temperature treatment, which includes a carbonization process and a sulfurization process;
[0019] The carbonization process is carried out in an inert atmosphere at a temperature of 700-900°C, a heating rate of 2-5°C / min, and a holding time of 1-3h;
[0020] The vulcanization process is carried out in an inert atmosphere at a temperature of 1200-1500° C., a heating rate of 2-5° C. / min, and a heat preservation time of 1-4 hours.
[0021] As a preferred scheme for the preparation method of sulfur-doped corn silk porous carbon, when the un-impurified sulfur-doped corn silk porous carbon is ultrasonically treated with hydrochloric acid, the hydrochloric acid concentration is 0.1-1.5 mol / L, and the ultrasonic time is 1-3 h; the drying temperature after the reaction is 80-100°C, and the time is 8-16 h.
[0022] A sulfur-doped corn silk porous carbon is prepared by any one of the preparation methods described above.
[0023] An application of sulfur-doped corn silk porous carbon. Based on the sulfur-doped corn silk porous carbon, the sulfur-doped corn silk porous carbon is used as a negative electrode material for sodium ion batteries.
[0024] The beneficial effects of the present invention are:
[0025] The present invention provides a sulfur-doped corn silk porous carbon and a preparation method and application thereof. Biomass waste corn silk is used as a carbon source, the corn silk is modified to achieve the recycling of the waste material, and the sulfur-doped corn silk porous carbon is successfully prepared by a one-step method using high-temperature treatment, which effectively reduces the operation steps and has the characteristics of simple process and low cost. At the same time, it can be processed in large quantities to achieve efficient utilization of resources.
[0026] The sulfur-doped corn silk porous carbon prepared by the present invention can also be used as a negative electrode material for sodium ion batteries. In the preparation process of sulfur-doped corn silk porous carbon, firstly, after high-temperature carbonization and sulfurization, corn silk can maintain the filamentous structure of the biomass itself, providing an excellent channel for the rapid conduction of electrons; secondly, the carbon thermal reduction reaction causes a large number of defects on the surface of the material, providing more active sites for the electrochemical reaction process; finally, sulfur doping causes the carbon material to have a CS bond, resulting in a larger interlayer spacing of the material, allowing sodium ions to be quickly transferred between carbon layers. Therefore, when sulfur-doped corn silk porous carbon is used as a negative electrode material for sodium ion batteries, the battery exhibits excellent performance such as high capacity and high rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0028] Figure 1is a SEM morphology image of sulfur-doped corn silk porous carbon prepared in Example 1 of the present invention;
[0029] Figure 2 This is an energy dispersive X-ray spectroscopy (EDS)-Mapping diagram of sulfur-doped corn silk porous carbon prepared in Example 1 of the present invention;
[0030] Figure 3 is an X-ray photoelectron spectrum (XPS) of the sulfur-doped corn silk porous carbon prepared in Example 1 of the present invention;
[0031] Figure 4 The sodium ion battery assembled by using the sulfur-doped corn silk porous carbon prepared in Example 1 of the present invention as the negative electrode material of the sodium ion battery is 1A·g -1 Down cycle performance test;
[0032] Figure 5 The results of rate performance tests of sodium ion batteries assembled using the sulfur-doped corn silk porous carbon prepared in Examples 1-3 of the present invention as the negative electrode material of sodium ion batteries;
[0033] Figure 6 The sodium ion battery assembled by using the corn silk carbon material prepared in Comparative Example 1 of the present invention as the negative electrode material of the sodium ion battery is 1A·g -1 Lower cycle performance test results;
[0034] Figure 7 The results of the rate performance test of a sodium ion battery assembled using the corn silk carbon material prepared in Comparative Example 1 of the present invention as the negative electrode material of the sodium ion battery;
[0035] Figure 8 This is a SEM morphology image of the corn silk carbon material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0036] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0037] The present invention will be further described below by means of specific examples.
[0038] A method for preparing sulfur-doped corn silk porous carbon comprises the following steps:
[0039] S100: washing, drying and crushing corn silk as a carbon source, and performing pre-carbonization treatment to obtain precursor A;
[0040] Specifically, the particle size of the carbon source is 300-600 mesh, preferably 500 mesh; the pre-carbonization temperature is 250-400° C., and the carbonization time is 2-5 hours. Preferably, the pre-carbonization treatment is carried out in a tubular furnace.
[0041] S200: ball milling the precursor A to obtain the precursor B;
[0042] Specifically, the ball milling time is 1 to 6 hours, and the rotation speed is 400 to 600 r / min.
[0043] S300: Precursor B is mixed with hydrochloric acid and stirred, washed with ultrapure water until neutral, and dried to obtain precursor C;
[0044] Specifically, the concentration of hydrochloric acid is 0.5 to 3 mol / L, the stirring temperature is 60 to 80° C., and the stirring time is 12 to 24 hours; the drying temperature after the reaction is 80 to 100° C., and the time is 8 to 16 hours.
[0045] S400: fully grinding the precursor C and sulfate, and subjecting them to high temperature treatment to obtain sulfur-doped corn silk porous carbon without impurities being removed;
[0046] Specifically, the mass ratio of sulfate to precursor C is (0.5-2.5):1; sulfate itself can exist as a salt template and react with carbon to increase the specific surface area of the carbon material. Therefore, sulfate is used as the sulfur source, and the sulfate is preferably potassium sulfate.
[0047] Specifically, the high temperature treatment includes a carbonization process and a sulfurization process; the carbonization process is carried out in an inert atmosphere, the temperature is 700-900°C, the heating rate is 2-5°C / min, and the holding time is 1-3h; the sulfurization process is carried out in an inert atmosphere, the temperature is 1200-1500°C, the heating rate is 2-5°C / min, and the holding time is 1-4h; the inert atmosphere is preferably an argon atmosphere. Preferably, the high temperature treatment is carried out in a tubular furnace.
[0048] S500: treating the unremoved sulfur-doped corn silk porous carbon with hydrochloric acid by ultrasonic treatment, washing with ultrapure water until neutral, and drying to obtain the sulfur-doped corn silk porous carbon;
[0049] Specifically, during the ultrasonic treatment, the hydrochloric acid concentration is 0.1-1.5 mol / L, and the ultrasonic time is 1-3 h; the drying temperature after the reaction is 80-100° C., and the time is 8-16 h.
[0050] Example 1
[0051] A method for preparing sulfur-doped corn silk porous carbon:
[0052] S100: Corn silk that has been washed, dried and crushed into 500 mesh size is used as a carbon source, and the carbon source is placed in a tubular furnace for pre-carbonization treatment. The pre-carbonization treatment is carried out in an argon atmosphere, and the temperature is raised from room temperature to 300°C at a heating rate of 3°C / min and a holding time of 3h to obtain precursor A.
[0053] S200: Precursor A was ball-milled at a rotation speed of 400 r / min for 2 h to obtain precursor B.
[0054] S300: Precursor B is stirred with 1 mol / L hydrochloric acid solution at 60°C for 24 hours. It is then washed with ultrapure water until neutral, and dried in an oven at 100°C for 12 hours to obtain precursor C.
[0055] S400: Precursor C and potassium sulfate were mixed in a mass ratio of 1:1, and after being evenly ground by grinding, they were placed in a tube furnace for high-temperature treatment, heating from room temperature to 800°C at a heating rate of 5°C / min, and holding time for 2h, and then heated to 1400°C at a heating rate of 5°C / min, and holding time for 2h. Unremoved sulfur-doped corn silk porous carbon was obtained.
[0056] S500: The obtained sulfur-doped corn silk porous carbon without impurities is taken out and ultrasonically treated with 0.1 mol / L hydrochloric acid for 1 hour, washed to neutrality, and then dried in an oven at 100° C. for 12 hours to obtain sulfur-doped corn silk porous carbon.
[0057] Sulfur-doped corn silk porous carbon was used as the negative electrode material for sodium ion batteries to assemble sodium ion batteries. Sulfur-doped corn silk porous carbon was used as the negative electrode material and glass fiber was used as the separator. 2025 button cells were assembled in the order of negative electrode shell - spring sheet - gasket - sodium sheet - electrolyte - separator - electrolyte - sulfur-doped corn silk porous carbon - positive electrode shell and the electrochemical performance was tested.
[0058] Example 2
[0059] A method for preparing sulfur-doped corn silk porous carbon:
[0060] S100: Corn silk that has been washed, dried and crushed into 300 mesh size is used as a carbon source, and the carbon source is placed in a tubular furnace for pre-carbonization treatment. The pre-carbonization treatment is carried out in an argon atmosphere, and the temperature is raised from room temperature to 250°C at a heating rate of 3°C / min and a holding time of 5h to obtain precursor A.
[0061] S200: Precursor A was ball-milled at a rotation speed of 500 r / min for 1 h to obtain precursor B.
[0062] S300: Precursor B is stirred with 0.5 mol / L hydrochloric acid solution at 80°C for 12 hours, then washed with ultrapure water until neutral, and dried in an oven at 90°C for 8 hours to obtain precursor C.
[0063] S400: Precursor C and sodium sulfate were mixed at a mass ratio of 1:2.5, and after being evenly ground by grinding, they were placed in a tube furnace for high-temperature treatment, heating from room temperature to 700°C at a heating rate of 2°C / min, and holding time for 3 hours, and then heated to 1200°C at a heating rate of 4°C / min, and holding time for 4 hours. Unremoved sulfur-doped corn silk porous carbon was obtained.
[0064] S500: The obtained sulfur-doped corn silk porous carbon without impurities is taken out and ultrasonically treated with 1 mol / L hydrochloric acid for 2 h. After washing to neutrality, it is dried in an oven at 80° C. for 16 h to obtain sulfur-doped corn silk porous carbon.
[0065] Sulfur-doped corn silk porous carbon was used as the negative electrode material for sodium ion batteries to assemble sodium ion batteries. Sulfur-doped corn silk porous carbon was used as the negative electrode material and glass fiber was used as the separator. 2025 button cells were assembled in the order of negative electrode shell - spring sheet - gasket - sodium sheet - electrolyte - separator - electrolyte - sulfur-doped corn silk porous carbon - positive electrode shell and the electrochemical performance was tested.
[0066] Example 3
[0067] A method for preparing sulfur-doped corn silk porous carbon:
[0068] S100: Corn silk that has been washed, dried and crushed into a 600-mesh size is used as a carbon source, and the carbon source is placed in a tubular furnace for pre-carbonization treatment. The pre-carbonization treatment is carried out in an argon atmosphere, and the temperature is raised from room temperature to 400°C at a heating rate of 3°C / min and a holding time of 2h to obtain a precursor A.
[0069] S200: Precursor A was ball-milled at a rotation speed of 600 r / min for 6 h to obtain precursor B.
[0070] S300: Precursor B is stirred with 3 mol / L hydrochloric acid solution at 70°C for 18 hours. Then, it is washed with ultrapure water until neutral, and dried in an oven at 80°C for 16 hours to obtain precursor C.
[0071] S400: Precursor C and potassium sulfate were mixed at a mass ratio of 1:0.5, and after being evenly ground by grinding, they were placed in a tube furnace for high-temperature treatment, heating from room temperature to 900°C at a heating rate of 4°C / min, and holding time of 1h, and then heated to 1500°C at a heating rate of 2°C / min, and holding time of 1h. Unremoved sulfur-doped corn silk porous carbon was obtained.
[0072] S500: The obtained sulfur-doped corn silk porous carbon without impurities is taken out and ultrasonically treated with 1.5 mol / L hydrochloric acid for 3 h, washed to neutrality, and then dried in an oven at 90° C. for 8 h to obtain sulfur-doped corn silk porous carbon.
[0073] Sulfur-doped corn silk porous carbon was used as the negative electrode material for sodium ion batteries to assemble sodium ion batteries. Sulfur-doped corn silk porous carbon was used as the negative electrode material and glass fiber was used as the separator. 2025 button cells were assembled in the order of negative electrode shell - spring sheet - gasket - sodium sheet - electrolyte - separator - electrolyte - sulfur-doped corn silk porous carbon - positive electrode shell and the electrochemical performance was tested.
[0074] In order to further illustrate the key points of this patent, a comparative case is added for illustration.
[0075] Comparative Example 1
[0076] The preparation process was basically the same as that of Example 1, except that potassium sulfate was not added to grind the precursor C to obtain corn silk carbon material.
[0077] The sulfur-doped corn silk porous carbons prepared in Examples 1-3 were subjected to electrochemical tests, and all had excellent electrochemical properties. The electrochemical properties of the sulfur-doped corn silk porous carbons as negative electrode materials for sodium ion batteries are shown in FIG. Figure 1-5 shown.
[0078] Figure 1 This is a SEM morphology of the sulfur-doped corn silk porous carbon negative electrode material prepared in Example 1. It can be seen that the fibrous structure of the corn silk itself can be maintained after carbonization, and there are obvious wrinkles on the surface of the material. The fibrous structure is conducive to the rapid conduction of electrons during the electrochemical reaction, and the wrinkles provide more adsorption sites.
[0079] Figure 2 The energy dispersive X-ray spectrum (EDS)-Mapping diagram of the sulfur-doped corn silk porous carbon prepared in Example 1 shows that the composite material mainly contains three elements: C, O, and S, and their mass percentages are 84.0%, 3.2%, and 12.8%, respectively. It can be seen that the S element has been successfully doped on the carbon material.
[0080] Figure 3 The XPS full spectrum and high-resolution spectrum of the sulfur-doped corn silk porous carbon prepared in Example 1 as the negative electrode material, where (a) the XPS full spectrum, (b) C 1s, (c) O 1s, and (d) S2p are high-resolution spectra. Figure 3(a) It can be seen that the sulfur-doped corn silk porous carbon negative electrode material contains three elements: C, O, and S. Among them, the O element mainly comes from the oxidation of the sample surface and the adsorption of water molecules in the air. There are four characteristic peaks in the high-resolution spectrum of C1s: CC (284.8eV), CS (285.82eV), OCO (290.4eV) and OC=O (293.73); the characteristic peaks in the high-resolution spectrum of O 1s include C=O (532.16eV), CO (533.7eV) and OH (537.1eV); the S2p spectrum shows that the S2p at 164.25eV and 165.47eV are respectively 3 / 2 Peak and S2p 3 / 2 In addition, S=O at 162.6 eV and C=S at 168.7 eV were also found in the S2p spectrum, indicating the successful preparation of S-doped porous carbon fibers.
[0081] Figure 4 When the sulfur-doped corn silk porous carbon prepared in Example 1 is used as the negative electrode material of sodium ion battery to assemble sodium ion battery, the battery is -1 The results of the constant current charge and discharge cycle test. As shown in the figure, the initial discharge capacity is as high as 399.8 mAh / g. After 600 cycles of charge and discharge, the discharge capacity drops to 305.99 mAh / g, and the capacity retention rate is 76.5%, indicating that sulfur-doped corn silk porous carbon used as a sodium battery negative electrode material exhibits good cycle stability.
[0082] Figure 5 The results of the battery rate performance test when the sulfur-doped corn silk porous carbon prepared in Example 1-3 is used as the negative electrode material of the sodium ion battery. As shown in the figure, at 0.05-2.0 A·g -1 The range increases stepwise, at 0.05, 0.1, 0.2, 0.5, 1.0, 2.0 A·g -1 The average discharge specific capacities at 0.1A·g were 320.5, 346.9, 354.5, 349.7, 342.2, and 325.3 mAh / g, respectively. -1 When the discharge capacity is 0.05-2.0A·g, the average discharge capacity still reaches 406.1mAh / g, showing a high rate performance. The capacity increase process can be attributed to the process of ion channels being opened during the charge and discharge process. -1 The range increases stepwise, at 0.05, 0.1, 0.2, 0.5, 1.0, 2.0 A·g -1 The average discharge specific capacities at 0.05-2.0A·g were 320.5, 306.1, 282.9, 259.7, 249.9 and 233.3mAh / g respectively. -1The range increases stepwise, at 0.05, 0.1, 0.2, 0.5, 1.0, 2.0 A·g -1 The average discharge specific capacities are 167, 155.3, 154, 150.8, 145.6, and 132.1 mAh / g, respectively. Compared with Example 1, the electrochemical performances of Examples 2 and 3 are not as good as that of Example 1, but both meet the application requirements.
[0083] The corn silk carbon material prepared in Comparative Example 1 was subjected to electrochemical testing. Figure 6-7 shown.
[0084] Figure 6 The sodium ion battery assembled by using the corn silk carbon material prepared in Comparative Example 1 without adding potassium sulfate as the negative electrode material of the sodium ion battery, at 1A·g -1 The constant current charge and discharge cycle test results. As shown in the figure, the initial discharge capacity is 367.5mAh / g. After 300 cycles of charge and discharge, the discharge capacity drops to 52.2mAh / g, and the capacity retention rate is 7.04%, indicating that the corn silk carbon material does not have good cycle stability when used as a negative electrode material for sodium battery.
[0085] Figure 7 The results of the rate performance test of the assembled sodium ion battery when the corn silk carbon material prepared without adding potassium sulfate in Comparative Example 1 is used as the negative electrode material of the sodium ion battery. As shown in the figure, the rate performance of the assembled sodium ion battery is 0.05-2.0A·g -1 The range increases stepwise, at 0.05, 0.1, 0.2, 0.5, 1.0, 2.0 A·g -1 The average discharge specific capacities at 0.1A·g were 185, 165.1, 134.5, 86.4, 52.2, and 36.7 mAh / g, respectively. -1 , the specific capacity is only 172.9 mAh / g, and the rate performance is significantly inferior to the test result of Example 1.
[0086] Figure 8 This is the SEM morphology of the corn silk carbon material prepared in Comparative Example 1. As shown in the figure, the untreated corn silk can still maintain a good fiber structure after carbonization, but a large amount of impurities are generated on the surface, and the generation of these impurities reduces the electrochemical properties of the material.
[0087] The above electrochemical test results show that when the sulfur-doped corn silk porous carbon provided by the present invention is used as a sodium negative electrode material for a sodium ion battery, the battery exhibits excellent electrochemical performance.
[0088] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing sulfur-doped corn silk porous carbon, characterized in that: The following steps are involved: The corn silk is washed, dried, and crushed as a carbon source, and pre-carbonized to obtain a precursor A; Ball milling the precursor A to obtain a precursor B; The precursor B is mixed with hydrochloric acid and stirred, washed with ultrapure water until neutral, and dried to obtain a precursor C; The precursor C and sulfate are fully ground and treated at high temperature to obtain sulfur-doped corn silk porous carbon without impurities being removed; The unremoved sulfur-doped corn silk porous carbon is ultrasonically treated with hydrochloric acid, washed with ultrapure water until neutral, and dried to obtain sulfur-doped corn silk porous carbon.
2. The method for preparing sulfur-doped corn silk porous carbon according to claim 1, characterized in that: The particle size of the carbon source is 300-600 meshes.
3. The method for preparing sulfur-doped corn silk porous carbon according to claim 1, characterized in that: The pre-carbonization temperature is 250-400° C., and the carbonization time is 2-5 hours.
4. The method for preparing sulfur-doped corn silk porous carbon according to claim 1, characterized in that: When the precursor A is ball-milled, the ball-milling time is 1 to 6 hours and the rotation speed is 400 to 600 r / min.
5. The method for preparing sulfur-doped corn silk porous carbon according to claim 1, characterized in that: When the precursor B is mixed with hydrochloric acid and stirred, the concentration of the hydrochloric acid is 0.5 to 3 mol / L, the stirring temperature is 60 to 80° C., and the stirring time is 12 to 24 hours.
6. The method for preparing sulfur-doped corn silk porous carbon according to claim 1, characterized in that: The mass ratio of the sulfate to the precursor C is (0.5-2.5): 1 。 7. The method for preparing sulfur-doped corn silk porous carbon according to claim 1, characterized in that: After the precursor C and potassium sulfate are fully ground, a high temperature treatment is performed, including a carbonization process and a sulfurization process; The carbonization process is carried out in an inert atmosphere at a temperature of 700 to 900°C, a heating rate of 2 to 5°C / min, and a holding time of 1 to 3 hours; The vulcanization process is carried out in an inert atmosphere at a temperature of 1200-1500° C., a heating rate of 2-5° C. / min, and a heat preservation time of 1-4 hours.
8. The method for preparing sulfur-doped corn silk porous carbon according to claim 1, characterized in that: When the unremoved sulfur-doped corn silk porous carbon is subjected to ultrasonic treatment with hydrochloric acid, the hydrochloric acid concentration is 0.1-1.5 mol / L, and the ultrasonic time is 1-3 h; the drying temperature after the reaction is 80-100° C., and the time is 8-16 h.
9. A sulfur-doped corn silk porous carbon, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. An application of sulfur-doped corn silk porous carbon, based on the sulfur-doped corn silk porous carbon according to claim 9, characterized in that: The sulfur-doped corn silk porous carbon is used as a negative electrode material for sodium ion batteries.
Citation Information
Cited By
Preparation method of sulfur-doped amorphous carbon nanosheet and application of sulfur-doped amorphous carbon nanosheet to negative electrode of sodium-ion battery
CN119750555A